The Role of the Government of Indonesia in Fighting for Recognition and the Right to Education for Children of Indonesia Migrant Workers in Malaysia - Moch. Iman Yulianto; Ardhana Januar Mahardhani; Sulton Sulton; Ikhwanudin Abdul Majid (Universitas Teuku Umar, 2023)
This study describes the role of the government and the struggle to get education for Indonesian citizens in Malaysia and to fulfill the right to education for the children of Indonesian Migrant Workers in Malaysia. There are several cases of children of Indonesian workers in Malaysia whose children's rights to education are not fulfilled, especially for illegal Indonesian migrant workers. In this study the authors used a qualitative research method - descriptive with the techniques used for data collection in the form of observation, interviews, and documentation. The results of the study show that the government has not been able to provide maximum facilitation for the children of illegal Indonesian workers so that the existence of non-formal learning centers in the form of guidance workshops plays a very important role in the achievement of migrant children who are struggling to get an education in Malaysia. From simple enrollment and low-cost tuition fees to many flexible solutions. This school is also considered to have fulfilled the indicators of achieving the right to education for the children of Indonesian workers, one of which is in the Gombak area, Selangor, Malaysia. The conclusion obtained in this study is that the government must guard the existence of Indonesian migrant workers in Malaysia with all its problems so that Indonesian migrant workers and their children can obtain proper education rights in accordance with policies issued by the government.